Estudio de los procesos productivos para optimizar la distribución de las áreas estratégicas de la planta “induce del ecuador”, ubicada en la ciudad de Latacunga, sector Tandalivi, periodo 2013 - Aymacaña Jami, Geovanny Álvaro (2014)
The study of production processes and distribution optimization strategic areas is a process that involves a technical analysis and proper distribution by which we throw quantitative results of the different processes according to a previously established method. Because the company does not have a proper distribution, it does not a suitable production process of this study needs to make immediate corrections or long term, if they are necessary. Implementation of Executive Order 2393 Regulations occupational safety and health of workers and improvement of the working environment are our basis for correcting the correct distribution of each workspace as worker safety itself, taking into account the period of work of each employee. This research project was developed in the Company INDUCE THE ECUADOR city of Latacunga, in order to conduct a study of production processes to optimize the distribution of strategic areas. The research is descriptive, whose techniques were interview, survey, field observation, the same were of great importance since it yielded data needed for the study of the problem. In conclusion by this proposal failed to identify, verify and organize each process areas; as to check the results back through an order and improve the production process by proper distribution and optimization of each area of growth for the company.